Disagreement and Flexibility: A Theory of Optimal Security Issuance and Capital Structure - Arnoud W.A. Boot; Anjan V. Thakor (Tinbergen Institute, 2003)
In this paper we introduce flexibility as an economic concept and apply it to the firm'ssecurity issuance decision and capital structure choice. Flexibility is the ability to makedecisions that one thinks are best even when others disagree. The firm's management valuesflexibility because it allows management to make decisions it believes are best forshareholders without being blocked by dissenters. The amount of flexibility management has atany point in time depends on how the firm is financed. Debt offers little flexibility relativeto equity. However, the flexibility offered by equity depends on the extent to whichshareholders are inclined to agree with management's strategic choices. Equity offers thegreatest flexibility when the propensity for shareholder agreement is the highest. It turnsout that the firm's stock price is also increasing in shareholders' propensity to agree withmanagement. Thus, the flexibility benefit of equity is high only when the sh!are price is high. The firm's optimal security-issuance choice trades off the flexibilitybenefit of equity against the now-familiar debt tax shield, and the firm's capital structure isthe consequence of a sequence of past security-issuance choices. The strongest implication ofthis theory of capital structure evolution is that optimal capital structure is essentiallydynamic, and depends on the firm's stock price, implying that firms issue equity when stockprices are high and debt when stock prices are low. The theory explains many stylized factsthat fly in the face of existing capital structure theories and also generates new testablepredictions. Moreover, the theory can rationalize the use of debt in the absence of taxes,agency costs or signaling considerations.
Keywords: D83; G30; G32; 330; Capital Structure; Security Issuance; Decision making.; Entscheidung; Fremdkapital; Kapitalstruktur; Theorie; Flexibilität